Terminals for railway signalling apparatus - British Standards Institution (London BSI, 1950)
Electric terminals, External, Railway signals, Railway equipment, Railway fixed equipment, Electrical components, Threaded components, British Association screw threads, Dimensions, Design, Brass, Nuts, Screws (bolts), Signal devices Railway applications
Confirmed, Current
Cross References BS 57, BS 93, BS 249, BS 488
Keywords: Railways Signals -- Standards